Prevalencia de los virus de inmunodeficiencia y leucemia en Felis catus en la clínica veterinaria centro médico veterinario del sur - Bravo Ruíz, Keyla Elizabeth (2025)
The present study aimed to determine the prevalence of Feline Immunodeficiency Virus (FIV) and Feline Leukemia Virus (FeLV) in domestic cats (Felis catus) treated at the Southern Veterinary Medical Center. Over a two-month period, blood samples were collected from 50 cats exhibiting clinical signs suggestive of FIV and FeLV infection. The samples were analyzed using the FIV Ab/FeLV Ag immunochromatographic assay to detect the presence of viral antigens and antibodies. The results were subsequently processed using descriptive statistics to assess the distribution of viral agents within the studied population, and the Chi-square test was applied to identify statistically significant associations between the presence of infection and selected variables. The findings revealed a prevalence of 36% for FeLV and 10% for FIV, indicating a higher occurrence of the former compared to the latter. No significant associations were observed between the presence of these infections and variables such as reproductive status, diet, or cohabitation with other cats, suggesting that transmission patterns are not strongly influenced by these factors. Hematological alterations were also reported in positive individuals—primarily anemia, erythrocytosis, leukocytosis, and thrombocytopenia in cats infected with FeLV, while leukocytosis and thrombocytopenia predominated in FIV-positive cats. These findings highlight the high prevalence of FeLV and the clinical impact of both infections on the feline hematopoietic system. They further underscore the importance of regular hematological monitoring in infected animals to enable timely and effective clinical intervention.